PENYUSUNAN LKS KEHIDUPAN KELUARGA KETERAMPILAN MEMBACA DAN MENULIS SMA/MA KELAS XI SEMESTER 1 - VANI MUKIN, VALERIANI (LATERNE, 2016)
The objective of this research is to create better students’ worksheets (LKS) that be able to be used on theme of family life for reading and writing skills in SMA/MA Eleventh Grades in the semester one. This research has done by the data collection in the field  that shows the process of studying German, especially on theme of family life in the MAN Bangkalan has not been used studenta’ worksheets (LKS) that is developed. Therefore, German teachers give advises to create development students’ worksheets (LKS) that be able to be enrichment for students or to be used  as the material of teaching learning process in the school. The research question of this study is how does create students’ worksheets (LKS) that be able to be in theme of family life to SMA/MA Eleventh grades in semester one.              The research design of this study use qualitative research design. This study bases on the steps to arrange students’ worksheets (LKS) by Diknas and  pays attention on the criterias to create students’ worksheets (LKS) by Badan Standar Nasional Pendidikan (BSNP) and the criteria to create appropriate students’ worksheets (LKS) by Darmojo and Kaligis. This students’ worksheets (LKS) has been validated by three expert of teaching material and the result of the validation is counted by using formula to know the percentage of students’ worksheets (LKS) validity. The result of the percetages is interpreted by score criteria interpretation by Riduwan.                This students’ worksheets (LKS) has construct validity in the 78,51% and content validity in the 72%. According to score criteria interpretation on the construct and content validity, This students’ worksheets (LKS) is valid to be used in school by paying attention on the validity points of students’ worksheets (LKS) that is still in the low level. Key words: students’ worksheets (LKS) arrangement, reading and writing skills